Reflexion und Metaperspektive als notwendige Komponente der Kartenkompetenz - Gryl, Inga; Horn, Michael; Schweizer, Karin; Kanwischer, Detlef; Rhode-Jüchtern, Tilman (Zeitschrift für Geographiedidaktik (ZGD), 2010)
Within the national educational standards of geography, the ability of reflection and of meta-perspective has a high significance. The competence to reflect is a skill that is called for development in almost every competence area. Against this background the contribution attempts to exemplify theoretical foundations and possible methodical approaches of a competence of reflection for map-reading. A map is being understood as a hybrid construction that combines textual and visual qualities. This in-between position and the comprehension of a map as a means of communication lead via a differentiation of the term map-reading to the competence of reflection, which is the ability and skill to read maps actively and appropriately. In order to achieve such a competence, methodical possibilities based on deconstruction and objective hermeneutics will be demonstrated. Moreover, the contribution provides an outlook of the ability of reflection within general competence models.